Kapłani i ich funkcje w Egipcie ptolemejskim w świetle archiwum świątyni w Soknopaiou Nesos - Wilimowska, Joanna (Instytut Historyczny Uniwersytetu Wrocławskiego, 2022)
Little is known about priests and how temples functioned in Ptolemaic Egypt. This paper provides an insight into the organisation and hierarchy of temples under the Ptolemies. The main aim of this paper is to providean overview of the titles and functions of temple personnel by analysing documents from the archive of the temple of Soknopaios and Isis Nepherses in the village of Soknopaiou Nesos (Dimeh).
Keywords: priests; temple personnel; Ptolemaic Period; Egyptian temples; Soknopaiou Nesos